Motricidad gruesa y el desarrollo cognitivo en la educación inicial I - Orbe Sarzosa, Fernanda Elizabeth (2017)
The initial education includes children between 3 to 4 years old, they are in appropriate ages for their physical and mental development which made possible to increase their efficiency and ability for learning. According to these stages are observed the cognitive child development through the usage of gross motor techniques, focused on determining the skills such as physical, mental, social and emotional needs of children. It carried out a diagnosis about the gross motor and cognitive development of children because of the initial education stage, children find in their bodies and movement the main things to come into contact with the reality at the same time learn, it is important to acquire the first knowledge about the world that are developing. The research was conducted at “Unidad Educativa de Desarrollo Integral del Cantón Mejía” located in Machachi - Mejía, Pichincha province in order to learn about the importance given to these areas which helped to strengthen the learning process in that institution....